Sistematización de la experiencia de intervención en talleres escuela san patricio a partir de talleres y acompañamiento en aula con docentes; para la promoción del buen trato durante el periodo de junio 2015 a marzo 2016 - Galárraga Chiriboga, Mischele Alejandra (2016)
The importance of the implementation of this project based on the promotion of good treatment with teachers TESPA, arises due to the detection of a crisis this institution, which is evident in the deterioration of interpersonal relationships in which between obvious features are that there are no good communication skills or forms, together with the structural crisis which has led to conflict and tension among its members. Thus the aim of the intervention was that by establishing a space for dialogue, in which teachers were the actors beneficiaries is achieved in the first instance to know the ways of existing in TESPA interaction, this was developed through workshops in that the problems that were based on the needs arising from the institution, these workshops were emerging proposals, which were to be worked in the classroom accompaniments, whose dynamics focused on allowing teachers reflected replicate what worked in the workshops. In such accompaniments it was possible to visualize the existence of a speech teacher empowerment and effectiveness of this in practice. Among the results of this intervention is awareness of the importance of management and development of good treatment, based on the interactions between teachers; teacher-students; teacher-institution; as well as the consolidation of my own learning.